The Geneva Conventions under assault - Perrigo, Sarah; Whitman, Jim, 1951- (Pluto Press, 2010)
Outrages committed during violent conflict and as part of the war on terror are not only an affront to human dignity -- they also violate the Geneva Conventions. This book examines recent high-profile cases of repeated and open abuse of theConvention.